2010
DOI: 10.1103/physreva.81.011802
|View full text |Cite
|
Sign up to set email alerts
|

Resonant interaction of a single atom with single photons from a down-conversion source

Abstract: We observe the interaction of a single trapped calcium ion with single photons produced by a narrow-band, resonant down-conversion source [A. Haase et al., Opt. Lett. 34, 55 (2009)], employing a quantum jump scheme. Using the temperature dependence of the down-conversion spectrum and the tunability of the narrow source, absorption of the down-conversion photons is quantitatively characterized.PACS numbers: 42.50. Ct, 42.50.Ex, 03.67.Bg At the level of single particles, the quantum nature of light-matter int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…At the same time, entangled SPDC photon pairs offer robust and simple generation of high-purity entanglement at a large rate and thereby serve as an optimal resource for communication over quantum channels [34][35][36][37]. In our previous work [38,39], we operated for the first time a hybrid quantum system integrating single trapped ions and SPDC photon pairs. We demonstrated absorption of single photons by the ion [38] and showed that the absorption of one photon from a pair can be heralded by the coincident detection of its partner photon [39]; time and frequency correlations of the photon pair are manifested in the heralded absorption process.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, entangled SPDC photon pairs offer robust and simple generation of high-purity entanglement at a large rate and thereby serve as an optimal resource for communication over quantum channels [34][35][36][37]. In our previous work [38,39], we operated for the first time a hybrid quantum system integrating single trapped ions and SPDC photon pairs. We demonstrated absorption of single photons by the ion [38] and showed that the absorption of one photon from a pair can be heralded by the coincident detection of its partner photon [39]; time and frequency correlations of the photon pair are manifested in the heralded absorption process.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental activities investigating the resonant interaction in free-space of a single atom with single photons produced through the spontaneous parametric down conversion (SPDC) have emerged in parallel [15][16][17]. In [18], the interaction of single heralded SPDC photons with a single atom has been demonstrated and in [19], the possibility of obtaining atom-photon entanglement from the absorption by a single atom of a photon belonging to a polarizationentangled SPDC pair has been shown.…”
Section: State Of the Artmentioning
confidence: 99%
“…For concreteness, we consider implementing the scheme using two distant single trapped and laser-cooled 40 Ca + ions. The 40 Ca + ion is the only single atomic system so far which has been coupled to entangled SPDC photons [17][18][19]. A scheme of its relevant atomic levels and transitions is shown in figure 2.…”
Section: Heralded Mapping Of Photonic Entanglement Into Single Atoms:mentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13], and for detecting the quantum state of trapped atoms [13,14]. Most recent experiments used quantum jumps in order to demonstrate single photon absorption by single trapped atoms [15], and analyzed their statistics in order to demonstrate quantum correlations between the absorbed photon and a second, entangled photon revealed at a detector [16]. Further experimental work used quantum jumps in the signal monitoring the number of photons inside a resonator as the basic element for implementing feedback loops, restoring the quantum state of a cavity mode [17].…”
Section: Introductionmentioning
confidence: 99%